2020
DOI: 10.1016/j.dld.2019.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Renal safety in 3264 HCV patients treated with DAA-based regimens: Results from a large Italian real-life study

Abstract: Background: Sofosbuvir (SOF)-based regimens have been associated with renal function worsening in HCV patients with estimated glomerular filtration rate (eGFR) ≤ 45 ml/min, but further investigations are lacking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…The same result has been recently reported in a real‐life cohort of 931 patients after a 12 weeks treatment with DAAs 51 . Moreover, treatment with sofosbuvir was associated with a reduction of e‐GFR in CKD stage 1 patients 52 and sustained e‐GFR decreases 12 weeks after treatment in one more series of patients 53 . Longer follow‐up is needed to explore the time trend of e‐GFR in patients treated with DAAs, but the potential benefits of DAA treatment outweigh the potential harms for patients with CKD stages 1‐3b, independently of the choice of DAA 54 …”
Section: Discussionsupporting
confidence: 86%
“…The same result has been recently reported in a real‐life cohort of 931 patients after a 12 weeks treatment with DAAs 51 . Moreover, treatment with sofosbuvir was associated with a reduction of e‐GFR in CKD stage 1 patients 52 and sustained e‐GFR decreases 12 weeks after treatment in one more series of patients 53 . Longer follow‐up is needed to explore the time trend of e‐GFR in patients treated with DAAs, but the potential benefits of DAA treatment outweigh the potential harms for patients with CKD stages 1‐3b, independently of the choice of DAA 54 …”
Section: Discussionsupporting
confidence: 86%
“…The overall eGFR ( Fig 2A ) of DAA-treated CHC patients decreased from the BL to EOT and P12 after DAA treatment. Several studies have revealed similar phenomena [ 9 , 11 , 13 ]. However, a decreased eGFR may not reflect true renal injury.…”
Section: Discussionmentioning
confidence: 74%
“…However, the short-term effect of DAA on renal function is inconclusive [ 5 , 6 ]. Several studies have reported that the estimated glomerular filtration rate (eGFR) might be reduced during DAA therapy, especially sofosbuvir (SOF) -based regimens [ 7 13 ]. However, some studies have revealed that the eGFR change might be nonsignificant [ 10 , 11 , 13 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, discordant results on renal function after HCV clearance by DAA were reported. In an Italian cohort study for 3264 patients treated with HCV by DAA with 96% achieved SVR [14], the eGFR was found decrease about 3 ml/min/1.73m 2 in all treated patients at SVR12, while the patients with CKD3A increased their eGFR about 2 ml/min/1.73m 2 and CKD3B increased about 1 ml/min/1.73m 2 at SVR12. Another cohort study for 1590 patients in Boston treated HCV with DAA and SVR12 (90.7%) [15] had overall eGFR improvement about 3 ml/min/1.73m 2 .…”
Section: Introductionmentioning
confidence: 97%